(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The current generation of epoxy resin-based sealers has drawbacks such as mutagenicity, cytotoxicity, inflammatory response, and hydrophobicity. Bioceramic-based sealers containing calcium silicate and calcium phosphate have recently received a lot of attention due to their physical and biological properties like alkaline pH, chemical stability in biological environments, and lack of shrinkage. The addition of calcium phosphate to bioceramic materials improves setting properties and results in a chemical composition and crystalline structure similar to tooth and bone apatite materials, which improves sealer-to-root dentin bonding. Bioceramic sealers were developed to overcome these disadvantages and have been proved to show better clinical performance. As a result, this review focuses on providing detailed insight into individual bioceramic sealers currently in use, as well as their properties.